Effect of Biocidal Substances on Population Dynamics of Plutella Xylostella Linnaeus, 1758, Auxiliary Insects, and Cabbage Production in the Suburban Area of Dakar - Faye, Mamecor; Diome, Toffene; Thiam, Guirane; Sembene, Mbacke (Journal of Asian Scientific Research, 2022)
This study was conducted to determine the effects of biopesticides, used in the control of Plutella xylostella, major bioaggressor of cabbage, on its auxiliaries as well as on cabbage quality. It took place in a field of 65 m2, located in Malika, peri-urban area of Dakar. Treatments, based on Crateva religiosa (200g/l), Calotropis procera (400g/l), a mixture of the two products, and the control, were performed every two weeks on a random block device. Analysis of the results was done with the Rstudio software. Results showed that untreated plots were more infested with Plutella xylostella larvae (p-value = 0.01271). Efficacy of Calotropis procera on P. xylostella larvae has been demonstrated. The effect was all the more interesting since auxiliaries were not affected by treatments, as the regular sampling revealed. A satisfactory agronomic result was obtained at the end of this test, with as indicator, a much larger harvest from the treated plots.